Study on the Preparation and Liquid Smoke Fluids Characterization as the Results of Pyrolysis from Sawdust - Sri Sugiarti; M. Nurhuda (Natural B, Journal of Health and Environmental Sciences, 2012)
There is a huge amount of biomass resources but it has not been utilized properly. For instance, converting it into liquid smoke. Liquid smoke is produced by pyrolysis process from four differences sawdust i.e. teak (Tectona grandis sp), mahagony (Switenia mahagoni jacq), jackfruit (Artocarpus heterophyllus lamk), and red sandalwood (Pterocarpus indicus). Pyrolysis process required 750-gram sawdust and performed for approximately 40 minutes.Percentage of liquid smoke production ranged from 26.51 ± 0.009% (mahagony) – 32.12 ± 0.009% (jackfruit). While, the charcoal produced ranged from 23.54 ± 0.008% (mahagony) – 34.76 ± 0.009% (jackfruit). The density value of liquid smoke produced ranged between 1014.996 ± 0.346 kg/m3 (mahagony) – 1019.408 ± 0.037 kg/m3 (teak).